Smok i panda. Hybrydyczny obraz Chin w polskich dyskursach współczesnych: Recenzja książki Doroty Brzozowskiej [2018] Chińskie ślady w polskich dyskursach współczesnych. - Pengjie, Qu (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article is a review of Dorota Brzozowska’s study Chińskie ślady w polskich dyskursach współczesnych (Chinese traces in Polish contemporary discourses). The in-depth analysis of the monograph attracts the reader’s attention to the wealth of the collected material and the multitude of viewpoints, but also points out certain inconsistencies the author failed to avoid which in turn led her to fall into the trap of excessive simplification and orientalisation of China.